4CPS-260 Introducing pharmaceutical care in a nursing home: impact analysis - Aguilar, E (Eur J Hosp Pharm, 2018)
BACKGROUND: Hospital Pharmacy Departments are providing pharmaceutical care since January 2017 for institutionalised patients in nursing homes (NH) in our region in order to optimise the available resources. The purpose of the pharmacist interventions (PI) is to improve the medication appropriateness in these patients, to adapt our Hospital Medicines Formulary (HMF) and to promote the rational use of drugs. PURPOSE: To describe PI regarding treatment prescribed for patients in a NH and to analyse its impact according to physicians’ acceptance. MATERIAL AND METHODS: Prospective, descriptive study conducted in a 140-bed NH from January to September 2017. Prescriptions were reviewed with the NH’s physician, and introduced in our e-prescribing program (e-PP). Patient and treatment data (sex, age, therapeutic groups, doses) were retrieved from e-PP management tool (inpatients’ clinical module). The following PI were described and registered: separate drug combinations (SdC), inclusion of new dose presentation in our HMF (iDP), dosage regimen modification (DRM), inclusion of new pharmaceutical form (iPF), change in the pharmaceutical form (cPF), pharmacological substitution according to HMS (PS), pharmacological substitution including a new drug in our HMF (iPS) and withdrawal of drugs not included in the HMF considered of low therapeutic value (LTV). RESULTS: We reviewed the prescriptions of 125 patients (71% males), mean age 72 years (61–95). We introduced 695 medical prescriptions in our e-PP, average number of medications per patient: 5.5 (0–16). A total of 262 PI were registered: 150 accepted, 112 rejected. Regarding most accepted PI we observed: 38% (55) iPS, 16.6% (25) iDP, 10.6% (16) PS, 10.6% (16) cPF, 10% (15) LTV and 9.3% (14) SdC. Only six PI were accepted for DRM, and one for iPF. Regarding pharmacological substitution, the most affected therapeutic groups were antihypertensives (28%), antidepressants (10.6%) and cholesterol-lowering agents (9.3%). CONCLUSION: Institutionalised patients in a NH are elderly and they present high prevalence of polypharmacy. The assessment of the acceptance of PI in this centre (57%) showed that the pharmacist will be a key element in offering integrated care for patients in a NH. The wide variety of antihypertensive drugs on the market leads to increasing efforts to adapt these prescriptions to our HMF. No conflict of interest